Studies on the amphipod genus Metopa (Stenothoidae) : Taxonomy, Ecology, Phylogeny - Tandberg, Anne Helene S. (University of Tromsø, 2011)
The papers of this thesis are not available in Munin. 1. Tandberg, A.H.S. and Vader, W.: 'A redescription of Metopa species (Amphipoda, Stenothoidae) based on the type material. 1. Zoological Museum, Copenhagen (ZMUC)', Zootaxa (2009) 2093:1-36. Available at http://www.mapress.com/zootaxa/ 2. Tandberg, A.H.S.: 'A redescription of Metopa species (Amphipoda, Stenothoidae) based on the type material. 2. The United States National Museum of Natural History (NMNH)', Zootaxa (2009) 2309:43-68. Available at http://www.mapress.com/zootaxa/ 3. Tandberg, A.H.S.: 'A redescription of Metopa species (Amphipoda, Stenothoidae) based on the type material. 2. The Natural History Museum Oslo (NHM)', Zootaxa (2010) 2465:1-94. Available at http://www.mapress.com/zootaxa/ 4. Tandberg, A.H.S., Schander, C. and Pleijel, F.: 'First record of the association between the amphipod Metopa alderii and the bivalve Musculus', Marine Biodiversity Records (2010) 3, e5. Available at http://dx.doi.org/10.1017/S1755267209991102 5. Tandberg, A.H.S., Vader, W. and Berge, J.: 'Metopa glacialis : an analysis of its ecology and its association with Musculus discors', Polar Biology (2010) 33:1407-1418. Available at http://dx.doi.org/10.1007/s00300-010-0833-9 6. Tandberg, A.H.S. and Vader, W.: 'Phylogenetic analysis of the stenothoid genera Metopa and Stenula (Crustacea, Amphipoda, Stenothoidae)' (manuscript) The Amphipod-genus Metopa is a relatively large genus, with currently 55 accepted species. This PhD thesis consists of redescriptions of 23 of these species based on typespecimens or specimens collected and identified by the original authors; this has been done to create consistent descriptions that could form a basis for a phylogenetic analysis of Metopa. For some species Scanning Electron Microscopy has been used to look for characters that have been overlooked by the original authors. The redescriptions are presented in 3 papers (Papers 1-3), with a phylogenetic analysis of 37 Metopa species (mostly based on personal examinations, but 6 based on literature-information) together with 6 Stenula species (partly based on literature, but most from examinations performed by Dr. Traudl Krapp-Schickel) presented in a manuscript (Paper 6). The result of the phylogenetic analysis is two clear clades (A and B), both including species from both original genera. This result could suggest a thorough change in stenothoid systematics, with the possible synonymization of Stenula into the older Metopa and erection of one or more new genera to include the species of clade A, but we have argued against doing this before further investigations have been undertaken. The stability of the resulting phylogeny is discussed, and in our opinion further studies are necessary to strengthen the conclusions reached here, before we formally make the necessarily very extensive nomenclatorial changes. However, the indications that Metopa and Stenula are paraphyletic are strong. Two papers (Papers 4-5) examine the ecology of Metopa species associated with mollusks. Paper 4 is a short note about findings of Metopa alderii inside the mussel Musculus spp., whereas Paper 5 is a more thorough discussion on the possible life history strategies for Metopa glacialis in its well known association with the mussel Musculus discors based on data collected by Svalbard. We show the presence of more than one broods in several examined mussels, and from the brood sizes and cohort compositions we suggest two possible scenarios: 3 or more seasons of single broods and parental care over more than 1 year after hatching, or multiple broods in one season and extended parental care. The introductory synthesis to the papers gives a short discussion of the papers, in addition to a historical introduction to both taxonomy and the amphipod-genus Metopa. A complete list of taxa that at some time have been included in Metopa is presented, this includes synonymies and references to the auctors and different authors who have moved the different taxa. There is also a table with biogeographical information about the genus, and the ecology of Metopa is discussed. A short discussion on molecular methods and the possible ways to ensure more data for a better phylogenetic analysis is also included.